Profile of Education and Breeding Experience with the Implementation of Seven Principles of Super Free-Range Chicken Breeding Business in Bone Bolango Regency - Fathan, Suparmin; Utina, Ramli; Mukhtar, Muhammad; Ahmad, Jusna; Hasim, Hasim; Latjompoh, Masra; Yusuf, Frida Maryati (Technium Social Sciences Journal, 2022)
The purpose of this study was to find the positive and significant effect of : 1) formal education (PF) on livestock experience (PB); 2) PF on the seven principles of business breeding super free-range chickens implementation (PSUBAKS); 3) PB towards PSUBAKS; and 4) PF through PB to PSUBAKS. The research was conducted in 29 villages in 8 sub-districts in Bone Bolango Regency. Respondents in total 76 farmers were determined using purposive sampling technique, with descriptive method, as well as hypotesis testing using Structural Equation modeling (SEM) with the help of Partial Least Square (PLS) to find out the positive and significant influence between variable in order to reveal the direct and indirect influence. Based on the findings can be concluded that : 1) PF has a positive and significant impact on PB; 2) PF has a positive and significant impact on PSUBAKS; 3) PB has a positive and significant impact on PSUBAKS; and 4) PF has a positive and substantial impact on PSUBAKS through PB.